Proposed business strategy for urbancut barbershop in semarang - Adhi Wibowo, Hajar; Toha, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract - UrbanCut Barbershop is a premium brand of barbershop that was established on May 4, 2013 under CV Ganesha Adhi Pratama. It was located at Tirto Agung Street, No. 12A, sub-district of Pedalangan, district of Banyumanik, Semarang of Central-Java. UrbanCut Barbershop was built to answer the need of modern man in Semarang area that need of a good representative haircut place with hygiene process and cozy place. UrbanCut Barbershop is a growing business and has big opportunity to success due to it has become pioneer in premium barbershop service in Semarang area. It showed by the number of customers that have been served and that increasing sales from its beginning they are opened until now. But, new problem start to come and the competition begin tougher. UrbanCut Barbershop sales performance basically is good and profitable enough for its owner. But owner feels that there have been a condition of sales revenue of UrbanCut after 8 months operation become stable or can be said it come to its optimum point. This phenomenon was discovered after UrbanCut Barbershop opened their second branch located in central business of Semarang area. Owner feels that this condition showed there are problem with UrbanCut Barbershop growing progress. The owner worry if the trend of sales in second branch becoming like the first store that reach its optimum point and donâ€™t grow anymore. Therefore, owner should initiate better strategy to keep increase sales growth and strategy for competes in Semarang Barbershop business. So, the focus of this research is to give UrbanCut Barbershop business strategy to solve their problem. First, author should determine what Urbancut Barbeshop business condition is and what about other external environment that affect their business. Second, author should give further strategy for UrbanCut Barbershop to win the business competition. The strategy objective are to define Arena for UrbanCut Barbershop; To Explore the differentiator factors in order to success; to plan the stages to win competition; To choose the best vehicle to reach the arena; To evaluate whether strategies will succeed in the business.Â Keywords: Barbershop industry, sales growth problem, internal and external environment analysis, growth strategy, diamond strategy consist of : arena, differentiator, vehicle, stage plan and economy logic.